YAP 5-methylcytosine modification increases its mRNA stability and promotes the transcription of exosome secretion-related genes in lung adenocarcinoma - Yu, Wenjun; Zhang, Congcong; Wang, Yikun; Tian, Xiaoting; Miao, Yayou; Meng, Fanyu; Ma, Lifang; Zhang, Xiao; Xia, Jinjing (Cancer gene therapy, 2023)
YAP is a transcriptional co-activator with critical roles in tumorigenesis. However, its upstream regulatory mechanism, especially how its mRNA stability is regulated, remains to be further studied. Here, we validated that YAP expression was higher in lung adenocarcinoma (LUAD) tissues compared to adjacent normal tissues, and found that YAP m 5 C modification occurred in its 328–331 3′ UTR region under the promotion NSUN2 and ALYREF, and increased the stability of YAP mRNA. This m 5 C modification also inhibited miR-582-3p binding and m 6 A modification in the nearby region. In addition, YAP m 5 C modification enhanced the exosome secretion effect, which was caused by two YAP-dependent transcription factors, Mycn and SOX10, and then stimulating the transcription of seven downstream exosome-promoting genes. Furthermore, we found that YAP m 5 C modification and its exosome-secretion-promoting function contributed to the malignant phenotype and AZD9291 (a third-generation EGFR-TKI) resistance of LUAD cells. Collectively, YAP is promoted by its m 5 C modification, and blocking YAP m 5 C modification will be helpful for future LUAD treatment. Briefly, YAP 3′UTR is m 5 C modified under the promotion of NSUN2 and ALYREF, and this modification increases YAP mRNA stability and inhibits nearby m 6 A modification and miR-582-3p binding. Furthermore, YAP stimulates seven exosome biogenesis, transport and release-related genes including HRS , PLD2 , RAB2B , RAB27A , RAB27B , VAMP and ATG7 in a Mycn- and SOX10-dependent manner.